MENYINGKAP DINAMIKA KINERJA KARYAWAN DARI PERSPEKTIF KEPEMIMPINAN DAN KEPUASAN KERJA [UNVEILING EMPLOYEE PERFORMANCE DYNAMICS FROM THE PERSPECTIVE OF LEADERSHIP AND JOB SATISFACTION] - Nurhidayat, M. Anton; Sopandi, Andi (Perkumpulan Ahli Bimbingan dan Konseling Islam Indonesia, 2025)
This study aims to analyze the influence of leadership and job satisfaction on employee performance at PT Herona Express South Tangerang. The research employs a quantitative associative method, utilizing a sample of 94 respondents selected through the Slovin formula from a total population of 123 employees. Data were collected via questionnaires and analyzed using multiple linear regression analysis facilitated by SPSS version 26 software. The results indicate that, partially, leadership plays a vital role in directing work effectiveness, where appropriate leadership styles are proven to significantly enhance individual performance. Similarly, job satisfaction was found to have a strong positive relationship with performance; employees who feel satisfied with their environment and compensation tend to provide more optimal contributions. Simultaneously, leadership and job satisfaction act as primary determinants that together dictate the quality of employee performance within the company. These findings suggest that a substantial portion of employee performance variation is driven by the quality of leadership and the level of job satisfaction, while the remaining factors are influenced by external variables not examined in this research. This underscores that to achieve maximum productivity, the management of PT Herona Express must prioritize developing leadership capacity and fulfilling factors that drive employee satisfaction.